Antioxidant Activity and Phenolic Content of Marine Dissolved Organic Matter and Their Relation to Molecular Composition - Catalá, Teresa S.; Rossel, Pamela E.; Álvarez-Gómez, Félix; Tebben, Jan; Figueroa, Félix L.; Dittmar, Thorsten (Frontiers in Marine Science, 2020)
The potential of marine dissolved organic matter (DOM) for free radical scavenging has been extensively evaluated, however the quantitative assessment of the antioxidant potential has been recently measured for the first time. The linkage of the DOM antioxidant potential to its molecular composition has not yet been examined. Following this line, this article takes a step forward by assessing, throughout a polarity-mediated fractionation, (1) the antioxidant capacity and phenolic content and (2) the molecular characterization of DOM in a more exhaustive manner. (3) The DOM antioxidant potential and phenolic content was linked to the molecular composition of DOM, which was molecularly characterized using ultrahigh resolution Fourier transform Ion Cyclotron Resonance mass spectrometry (FT-ICR MS). Antioxidant activity and phenolic content were quantified by the free radical 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and the Folin-Ciocalteu methods, respectively. We considered three types of different natural DOM samples: the deep North Pacific Ocean, the oligotrophic surface of the North Pacific Ocean and porewater from the sulfidic tidal flats of the Wadden Sea. Bulk porewater and its individual polarity fractions presented the highest antioxidant activity and phenolic content. DOM from the water column samples had lower antioxidant activity and phenolic content than porewater, but exceeded what it is commonly found in macroalgae and microalgae or fruits and vegetables with cosmeceutical purposes. Our values were similar to published values for terrestrial DOM. The variations in bioactivity were dependent on polarity and molecular composition. The high resolution and high mass accuracy used to determine the molecular composition of marine DOM and the chemometric and multistatistical analyses employed have allowed to distinguish molecular categories that are related to the bioactive potential. As a future perspective, we performed cytotoxicity tests with human cells and propose marine DOM as a natural ingredient for the development of cosmeceutical products.